Nipah Virus Infection in Asia: A Review Update - Akhter, Poly (Bangladesh Journal of Infectious Diseases, 2023)
The Nipah virus is extremely virulent and has been linked to neurological and respiratory diseases in both humans and animals. Fruit bats, virus-containing fruit and date juice consumed by animals, as well as airborne droplets, are the main sources of the virus's dissemination. Over the previous decades, Asian countries have experienced several epidemics and significant fatality rates. Additionally, the Nipah virus infection disrupted the socio-economic progress of the affected nations, which hinders the achievement of the SDGs. Bangladesh Journal of Infectious Diseases, June 2022;9(1):31-37